Determination of folic acid level in some foodstuffs - Karatas, F.; Cansiz, A.; Cifci, H.; Serbetci, Z. (Springer, 2007)
[Abstract Not Available]
Keywords: Cardiovascular-Disease; Folate; Cancer; Food; Risk; Hplc